From the Editor, April 2025 - Peace, Christopher (New Zealand Journal of Health and Safety Practice, 2025)
Welcome to volume 2, edition 1 of the New Zealand Journal of Health and Safety Practice. I make no apologies for this lengthy editorial. There is much to comment on and good articles to read. Our logo represents a kete – a basket – and this edition is another basket of knowledge.